2015
DOI: 10.1016/j.tvjl.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Development of a serological ELISA using a recombinant protein to identify pig herds infected with Brachyspira hyodysenteriae

Abstract: Development of a serological ELISA using a recombinant protein to identify pig herds infected with brachyspira hyodysenteriae, The Veterinary Journal (2015), http://dx.doi.org/doi: 10.1016/j.tvjl.2015.08.021. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
0
5
0
1
Order By: Relevance
“…64 65 Enzyme-linked immunosorbent assays (ELISAs) have the potential to be used for quantifying 66 serum antibodies to pathogens, and hence providing indirect evidence of past exposure to the 67 pathogen. As a consequence they are very useful in routine screening of apparently healthy 68 animals at the abattoir to assess the likely status of the herd of origin, particularly where the 69 be widespread amongst B. hyodysenteriae strains and to have potential to be used as an ELISA 83 antigen to detect infected herds (Song et al 2015). In the current study a prototype test using 84 H114 developed by Prionics AG (Priocheck ® Brachyspira porcine Ab ELISA) was tested on 85 sera from pigs in 30 herds with or without a history of having SD.…”
Section: Introduction 43mentioning
confidence: 99%
“…64 65 Enzyme-linked immunosorbent assays (ELISAs) have the potential to be used for quantifying 66 serum antibodies to pathogens, and hence providing indirect evidence of past exposure to the 67 pathogen. As a consequence they are very useful in routine screening of apparently healthy 68 animals at the abattoir to assess the likely status of the herd of origin, particularly where the 69 be widespread amongst B. hyodysenteriae strains and to have potential to be used as an ELISA 83 antigen to detect infected herds (Song et al 2015). In the current study a prototype test using 84 H114 developed by Prionics AG (Priocheck ® Brachyspira porcine Ab ELISA) was tested on 85 sera from pigs in 30 herds with or without a history of having SD.…”
Section: Introduction 43mentioning
confidence: 99%
“…Several prototype B . hyodysenteriae enzyme-linked immunosorbent assays (ELISA) have been developed to detect antibodies circulating in sera [ 32 34 ]. An Australian field study [ 33 ] showed that seroprevalence varies from <5% to 100% in both reported SD-negative and reported SD-positive farms indicating that serum profiling is most suited for herd-level investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation and marked differences in antigenic proteins are significant limitations for development of a globally applicable serological test [36]. Some studies using recombinant proteins have been carried out to develop a serological test that would be an important tool for detecting B. hyodysenteriae positive herds without clinical signs of SD [21,37].…”
Section: Discussionmentioning
confidence: 99%